2021
DOI: 10.1177/0898264320988187
|View full text |Cite
|
Sign up to set email alerts
|

Does Early Life Racial Discrimination Explain a Mental Health Paradox among Black Adults?

Abstract: Objectives: To evaluate the impact of early life racial discrimination (ELRD) on mental health among Black adults. Methods: Data were from the Nashville Stress and Health Study ( n = 618). Ordinary least squares regression models examined the relationship between ELRD and adult psychological distress; logistic regression estimated the probability of past-year major depressive disorder (MDD). We also assessed whether ELRD moderated the relationship between adult discrimination and mental health. Results: Childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 69 publications
(98 reference statements)
0
17
0
Order By: Relevance
“…However, even with the broad range of experiences considered to be ELA in these studies, they do not capture the diversity of adversity experienced by the global population or even within the United States. More recent studies have added to the list of adverse childhood experiences that increase the risk of health problems, such as bullying by peers ( Biedermann et al, 2021 ; Iob et al, 2021 ), being involved in an environmental disaster ( Adebäck et al, 2018 ), being treated for a chronic illness ( Bergmans and Smith, 2021 ), being subjected to family separation due to parental incarceration within countries ( Murray and Farrington, 2008 ; Swisher and Shaw-Smith, 2015 ) and at the US-Mexico border ( Teicher, 2018 ; de la Peña et al, 2019 ; MacLean et al, 2020 ; Sidamon-Eristoff et al, 2022 ), economic hardship ( Mawson and Gaysina, 2021 ), neighborhood violence ( van Rooij et al, 2020 ), and racism ( Thomas Tobin and Moody, 2021 ).…”
Section: The Link Between Early Life Adversity and Negative Health Ou...mentioning
confidence: 99%
“…However, even with the broad range of experiences considered to be ELA in these studies, they do not capture the diversity of adversity experienced by the global population or even within the United States. More recent studies have added to the list of adverse childhood experiences that increase the risk of health problems, such as bullying by peers ( Biedermann et al, 2021 ; Iob et al, 2021 ), being involved in an environmental disaster ( Adebäck et al, 2018 ), being treated for a chronic illness ( Bergmans and Smith, 2021 ), being subjected to family separation due to parental incarceration within countries ( Murray and Farrington, 2008 ; Swisher and Shaw-Smith, 2015 ) and at the US-Mexico border ( Teicher, 2018 ; de la Peña et al, 2019 ; MacLean et al, 2020 ; Sidamon-Eristoff et al, 2022 ), economic hardship ( Mawson and Gaysina, 2021 ), neighborhood violence ( van Rooij et al, 2020 ), and racism ( Thomas Tobin and Moody, 2021 ).…”
Section: The Link Between Early Life Adversity and Negative Health Ou...mentioning
confidence: 99%
“…We found that African Americans presented with the highest number of multimorbidities at an earlier age than patients of other race/ethnicities, consistent with results observed in other studies 6 . African Americans are exposed to more traumatic experiences and stressors, such as discrimination and poverty, earlier on in life, which produces additional health risks and contributes to worse health outcomes in later life 45 , 46 . Although mental health disorders are not prevalent, the earlier emergence of multimorbidity could result from psychological distress at an earlier age 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, although this study recognized the essential role of exposure to social stressors in the development of psychosocial resilience over the life course, stress exposure was not directly assessed. Early life adversity may be an important mechanism through which resilience is developed and maintained over time ( Thomas Tobin & Moody, 2021 ; Turner et al, 2016 ; Umberson et al, 2015 ). Additional research is needed to evaluate the significance of lifetime stress exposure for shaping African American men’s resilience.…”
Section: Discussionmentioning
confidence: 99%